DETERMINAN BUDGETARY SLACK PADA SATUAN PERANGKAT DAERAH KABUPATEN BANYUWANGI - Irmawati, Lidiya (Fakultas Ekonomi, 2024)
This research aims to determine the influence of budget participation, information asymmetry, budget emphasis, and clarity of budget targets on budgetary slack in SKPD Banyuwangi Regency. This research used a Cluster Sampling sampling technique with a total of 81 respondents, consisting of heads of departments/agencies, treasurers, heads of planning sub-divisions. Data collection used a questionnaire research instrument using Likert scale measurements. Data analysis in this study used SPSS V.25.The research results show that simultaneously the variables Budget Participation, Information Asymmetry, Budget Emphasis, and Clarity of Budget Targets have a significant effect on Budgetary Slack. Meanwhile, partially the variables Budget Participation, Budget Emphasis, and Clarity of Budget Targets have no effect on Budgetary Slack, and the Information Asymmetry variable has a positive effect on Budgetary Slack.